The Essence and Interaction Mechanisms of Subjects of Education in Forming the Personality of Students of the Educational Organization of the Ministry of Internal Affairs of Russia - Konopleva, E.A. (Bulletin of Practical Psychology of Education, 2021)
The article reveals the issues of educational work with students of educational organizations of the Ministry of Internal Affairs of Russia. The educational process is considered as the implementation of a scientifically grounded and normatively regulated system of measures for the moral and professional-psychological preparation of the personality of the future employee of the Internal Affairs agencies for professional activity. The realities of the current moment impose very high requirements on the personality of an employee of the Internal Affairs agencies, and therefore this personality requires not only detailed study, but also a constant system-built psychological and pedagogical influence. The specifics of law enforcement is determined not only by the tense organizational, intellectual and emotional situation, but also by the need to act at the intersection of ethics and law, moral and legal regulation. At the same time, educational work with students, as a system of purposeful psychological and pedagogical influence on the consciousness, feelings and behavior of a person, should be carried out with the maximum consideration of individual characteristics. The solution of these problem areas, as well as the implementation of the most important task of personal education-interiorization of values, is possible when using an integrated approach in support of educational activities, where the leading role is assigned to the moral and psychological support of educational activities. В статье раскрыты вопросы воспитательной работы с обучающимися образовательных организаций МВД России. Воспитательный процесс рассматривается как осуществление научно обоснованной и нормативно регламентированной системы мер по нравственной и профессионально-психологической подготовке личности будущего сотрудника органов внутренних дел к профессиональной деятельности. Реалии текущего момента предъяв-ляют к личности сотрудника органов внутренних дел очень высокие требования, в связи с чем эта личность требует не только детального изучения, но и постоянного системно выстроенного психолого-педагогического воздействия. Специфика правоохранительной деятельности обусловлена не только напряженной организационной, интеллектуальной и эмоциональной обстановкой, но и необходимостью действия на стыке этики и права, морального и правового регулирования. В то же время, воспитательная работа с обучающимися как система целенаправленного психолого-педагогического воздействия на сознание, чувства и поведение человека должна осуществляться с максимальным учетом особенностей личности. Решение данных проблемных зон, а также реализация важнейшей задачи воспитания личности — интериоризации ценностей возможны при использовании комплексного подхода в сопровождении учебной деятельности, где ведущая роль отведена морально-психологическому сопровождению учебной деятельности.